Um mecanismo de tratamento de exceções sensível ao contexto aplicado a internet das coisas - Gomes, Gabriel Henrique Faustini (Universidade Federal de São Carlos, 2020)
Internet of Things (IoT) devices, which can range from smart watches to health monitors, are increasingly intrinsic and ubiquitously connected in people’s routine. With such ubiquitous devices and applications growing in numbers, and our society increasingly relying on such systems ubiquitous, a number of software development challenges have emerged. More sophisticated applications should be able to control and exploit the dynamics of changing contextual information of users and the surrounding environment. Thus, such systems need to meet stringent requirements related to application-specific fault tolerance, integrity, and availability. This fundamental issue in the development of reliable ubiquitous systems lies in how properly handle application errors in the presence of frequent contextual changes and asynchronous communication. In this context, aiming to overcome these inerent challenges, this research proposes a Context-aware Exception Handling (CAEH) Mechanism Applied to Internet of Things. The mechanism consists of publish/subscribe middleware to communicate the devices in conjunction with a proposed architecture to handle contextual exceptions. The validation of the proposed CAEH mechanism was accomplished through the development of a the simulation of a practical application (case study) that explore and evaluate its use in the construction of context-sensitive asynchronous systems. All source code as the simulation was made available on a platform so that developers can use the guidelines created to implement exception handling.
A context-aware exception handling mechanism applied to internet of things
Keywords: Dispositivos móveis; Internet das coisas; Tratamento de exceções; Sensibilidade ao contexto; Mobile devices; Internet of things; Exception handling; Context-aware; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::TEORIA DA COMPUTACAO